STABLE CARBON ISOTOPE RATIO (δ13C) OF SHALLOW MARINE BOTTOM SEDIMENT AS EVIDENCE OF POLLUTION IN MANORA CHANNEL, KARACHI, PAKISTAN - Mashiatullah, A.; Javed, T.; Chaudhary, M. Z.; Fazil, M.; Qureshi, R. M. (The Nucleus, 2010)
Marine sediments are one of the endpoints for domestic /industrial contaminants from land based sources and provide an archive for tracing pollution record. Contaminated sediment is a significant environmental problem affecting many marine ecosystem. In the present study sediment samples from Manora Channel/Karachi harbour were analyzed for stable isotope composition of inorganic and organic carbon fractions (measured as δ 13C) to estimate the land based terrestrial organic matter in the Manora Channel. The principle of this application lies in the fact that δ 13C values of inorganic carbon (mineral fractions such as calcite, aragonite, dolomite) differs vastly from that of the organic carbon fraction of domestic and/or industrial origin in the sediments. Relatively more depleted δ 13C (organic) values ranging between - 30.65 to -19.27 ‰ PDB for the organic carbon fraction were found in the Layari river outfall zone. In Manora channel mains enriched values δ 13C was found in sediment of Manora lighthouse (-5.0 ‰ PDB) and Pakistan Naval Academy (-11.76 ‰ PDB) while in same zones depleted values of δ 13C was found in Bhabba island (-27.31‰ PDB), Bhit Island (-26.13‰ PDB) and Boat Club area (-23.08‰ PDB) indicating impact of domestic sewage added to the Manora channel from surrounding Islands. δ 13C (inorganic) fraction of sediment follow similar trend. In conclusion, this study indicates that the bottom sediments of Karachi Harbour and Layari river outfall zones are mainly polluted with organic waste of domestic origin derived from Layari river.